Cancer : the role of genes, lifestyle, and environment - Panno, Joseph (New York : Facts On File, 2005)
Discusses common types of cancer, cancer cells, oncogenesis, cancer progression, therapies, cancer around the world, and clinical trials, and presents overviews of related topics, including eukaryote cells, recombinant DNA, gene therapy, matching tissues, and the Human Genome Project.
Includes bibliographical references and index.
Wilson's Senior High School.
Young Adult
Keywords: Cancer -- Environmental aspects; Cancer -- Genetic aspects; Cancer -- Social aspects; Cancer -- Environmental aspects; Cancer -- Genetic aspects; Cancer -- Social aspects